The Philosophies of Regional Integration: European Union, Mercosur, Brics (PerCursos, 2025)
For many decades, the forms of regional integration in Europe were presented as the ideal-typical model for all other integration experiences worldwide, including in Latin America. Today, however, the picture has changed dramatically. The European Union is undergoing a genuine “organic crisis.” This is not a conjunctural crisis, linked to one of the many recurring emergencies affecting the Old Continent, but rather a structural crisis that strikes at the very core of its legitimacy: the welfare state, increasingly sacrificed in the name of a war economy. It is precisely in this context that there is a need to attempt a bold “knight’s move” by initiating a dialogue with the BRICS, which represent an innovative form of integration among states belonging to different regional areas of the world.
Keywords: regional integration; organic crisis; welfare state; Brics; Mercosur